Solve for *x* :

`3/(x+1)+4/(x-1)=29/(4x-1);x!=1,-1,1/4`

Advertisement Remove all ads

#### Solution

`3/(x+1)+4/(x-1)=29/(4x-1)`

`=>(3(x-1)+4(x+1))/((x+1)(x-1))=29/(4x-1)`

`=>(3x-3+4x+4)/((x+1)(x-1))=29/(4x-1)`

`=>(7x+1)/(x^2-1)=29/(4x-1)`

⇒(7x+1)(4x−1)=29(x^{2}−1)

⇒28x^{2}+4x−7x−1=29x^{2}−29

⇒28x^{2}−3x−1=29x^{2}−29

⇒x^{2}+3x−28=0

⇒x^{2}+7x−4x−28=0

⇒x(x+7)−4(x+7)=0

⇒(x+7)(x−4)=0

⇒x+7=0 or x−4=0

⇒x=−7 or x=4

Concept: Solutions of Quadratic Equations by Factorization

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads